ANALISIS FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN IBU NIFAS DALAM MENGKONSUMSI VITAMIN A: Juliyanti, Syarifah Ismed, Titin Dewi Sartika , Siti Aisyah Hamid (Biro Riset, Inovasi dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2021)
One of the efforts to treat vitamin A deficiency in postpartum women is by giving vitamin A capsules to postpartum women twice. Postpartum mothers who get enough vitamin A will increase the content of vitamin A in breast milk (ASI), so that breastfed babies are more immune to disease. In addition, the mother recovers her health faster. The purpose of this study was to determine the relationship between knowledge, education, attitudes of postpartum mothers and the role of midwives simultaneously with adherence to vitamin A consumption in the Work Area of ??Talang Pangeran Health Center, Ogan Ilir Regency in 2021. This type of research uses an analytical survey with a cross sectional approach. The sample size in this study was 59 respondents' mothers taken by accidental sampling. Data analysis using univariate analysis and bivariate analysis using chi square test. The results of the study showed that there was a relationship between knowledge (p value = 0.022), education (p value = 0.007), postpartum mother's attitude (p value = 0.013) and the role of midwives (p value = 0.038) with adherence to vitamin A consumption in the Talang Pangeran District Health Center Work Area. Ogan Ilir.